Roussea’s Influence in the Kantian System of Practical Reason - Plata Pineda, Oswaldo (Estudios de Filosofía, 2008)
This paper considers the influence of Rousseau on the practical Kantian System Theory. In my opinion, The Rousseau influence proves to be more moral than the Methodological influence (Hume) and Epistemo- logical influence and as a result of this, the practice as conceived in “The Canon of Pure Reason” acquired a superlative importance in the Kantian’s System. As such, this thesis defends that Rousseau, more than Hume and Newton supplied the key to the final constitution of the Philosophical System of Kant.